Penyuluhan Pentingnya Peran Orangtua dalam Penanaman Akhlak Mulia pada Anak di Rumah Singgah Al-Maun Bengkulu - Anwar Hakim (CV. Doki Course and Training, 2024)
Community service activities through counseling about the importance of the role of parents in instilling noble morals in children aim to provide education and knowledge about the importance of noble morals in children as a provision for the young generation of Muslims in society in the future. This activity is in line with the Tri Dharma of Higher Education as part of the role of coaching the community. This activity is important to be carried out as part of the lecturer's obligation in carrying out the duties of the Tri Dharma of Higher Education, as well as an effort to educate the public about the importance of the role of parents in instilling noble morals in children so that they can fortify the children of the Muslim generation from the entry of outside culture which results in the destruction of the morals of the Muslim generation. This service activity was carried out at the al-Maun Bengkulu Shelter. This service activity is carried out by counseling methods through lectures, direct question and answer interactions so that it makes it easier for mothers and children present to understand the material presented and can directly discuss questions and answers on various problems about morals. With the implementation of this service activity, parents become aware of the importance of the role of parents in instilling moral values in their children and the children become aware of various noble morals in Islam that must be possessed by them as candidates for the next generation in the future.